Copper distribution in a river system that receives coal mine-affected water releases in the Fitzroy River Basin, Central QLD - Jones, CE; Vicente-Beckett, VA; Chapman, JM; Bennett, WW (SETAC-AU, Australia, 2016)
The Mackenzie River sub-basin in the Fitzroy Basin (Central Queensland) is a turbid river system associated with significant coal mining. Coal mine-affected water (CMAW) releases do not occur during low flow conditions. Copper (Cu) is one of the heavy metals found in CMAW. The median annual dissolved Cu concentrations in the Mackenzie basin during low flow conditions in 2010-2014, calculated from data reported by the Fitzroy Partnership for River Health, were 3.0, 2.0, 1.5 and 1.2 µg/L (n = 43–264), respectively, with concentrations for 3 years being greater than the ANZECC (2000) toxicant trigger value for Cu (1.4 µg/L) for slightly-moderately disturbed freshwater systems. This study sought to determine the potential bioavailability and the distribution of Cu in the Mackenzie River environment. Two field trips were conducted: sediment core samples were taken in August 2014 and water samples in March 2015, both during low flow conditions and no recent CMAW releases. Three sites were sampled: one, in an upstream tributary, where no coal mining activity existed (called “Ref” site), and two downstream Mackenzie River sites (Site 5b and Site 6), that could receive cumulative mine-affected water releases, from numerous upstream coal mines. DGT-labile Cu (using DGT devices), total dissolved Cu (grab water samples filtered through 0.45µm at the site) and Cu in suspended particulate matter (retained on large diameter 0.45 µm filters, in field) were measured at each site. Triplicate DGT samplers were deployed for 48 h, and triplicate grab water samples were taken during deployment and retrieval of the DGT devices at each site. There was no significant difference in the total dissolved Cu concentration at deployment vs at retrieval at the Ref site and at Site 6 (furthest downstream). The average dissolved Cu concentration over 48 h at these two sites were 0.91 ±0.10 µg/L and 1.6 ±0.26 µg/L, respectively. In contrast a significant difference in the Cu concentration at deployment vs at retrieval was observed at Site 5b (2.1 ±0.14 µg/L vs 3.2 ±0.42 µg/L). Total dissolved Cu at Ref site was below the ANZECC (2000) trigger value, whereas concentrations at downstream sites were greater than the trigger value. The time-averaged DGT-labile (or potentially-bioavailable) Cu concentrations were low overall, being greatest at Site 5b (0.37 ±0.04 µg/L) and similar at Ref site and Site 6 (0.20 ±0.09 vs 0.18 ±0.01 µg/L, respectively). The Ref site had 4.3 mg/kg of particulate Cu on deployment and 1.3 mg/kg on retrieval; the respective values for Site 5b were 2.8 and 9.8 mg/kg, and for Site 6 were 1.2 and 2.1 mg/kg. Turbidity readings on retrieval were 27.4, 163 and 127 NTU at the three sites, respectively. A 10-cm sediment core from Ref site and a 12-cm core from Site 6 were analysed; Site 5b had rocks and pebbles and was unsuitable for coring. Cu concentration (<60 µm fraction) in the 2-cm core slices from Ref site ranged from 16.9-37.7 mg/kg dry weight (dw), and in Site 6 from 19.5-28.3 mg/kg dw. This preliminary study has demonstrated that total dissolved Cu in grab water samples may overestimate the potential impact of Cu on the aquatic environment. Cu distribution in different phases of the turbid Mackenzie River system indicated low bioavailable-Cu levels during low flow conditions. Comparative testing during CMAW releases is recommended. Cu concentrations (<60 µm fraction) in sediment cores were relatively low.